AN ANALYSIS OF SLANG WORDS USED IN BLACK PANTHER MOVIE - Krisdianka, Bob; Ras, Fakhri; Syarfi, Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Slang is confidential, informal English spoken which created and used by a particular community. This study discusses about an analysis of slang in Black Panther movie. The purpose of this study is to find the type and the meaning of slang used in a Black Panther movie. The source of the data was taken from the script of Black Panther movie. The Black Panther movie is classified as African action movies released on 14th February 2018 and directed by Ryan Coogler. The research design used in this study is descriptive qualitative research with a document or content analysis as the research type. This thesis described one by one word or phrase of slang found from Black Panther movie by using dictionaries and theory related about slang.From the analysis, there were three types of slangs, they were society slang, public house slang, and soldier slang. There were 8 words of society slang, 6 words of public house slang, and 1 word of soldier slang. Then the slang term in the form of words and phrases were classified and analyzed. The finding shows that there are some words and phrases of slang in Black Panther that have been classified into types of slang. The examples are Strap, Shit, Freeze, Baba, Guy, Chicks, Mate, and Feds.This research is expected to contribute to the reader's clear knowledge of slangs. It can assist the reader to talk fluent English. And fresh English vocabulary used in the daily discussion can also be anticipated to be enriched.Key Words: Slang, Movie, Black Panther